NUMERICAL INVESTIGATION OF EFFECTS OF THE INLET VELOCITY MAGNITUDE ON THE RECOVERY (STABILIZATION) TIME OF THE UNIDIRECTIONAL AIRFLOW, WHICH WAS DISTURBED BY THE OPERATOR MOVEMENT IN A CRITICAL ZONE - Evgeny V. Cherniakov (Вестник Северо-Кавказского федерального университета)
This study deals with the influence of static and dynamic objects on the airflow (generated by a unidirectional air supply with different velocities of the air, from 0.1 to 1.0 m/s) inside a cleanroom space.